Molecular Mechanism Underlying the Plant NRT1.1 Dual-Affinity Nitrate Transporter - Sun, Ji; Zheng, Ning (Frontiers in Physiology, 2015)
Nitrate (NO3−) is one of the most important sources of mineral nitrogen, which also serves as a key signaling molecule for plant growth and development. To cope with nitrate fluctuation in soil that varies by up to four orders of magnitude, plants have evolved high- and low-affinity nitrate transporter systems, consisting of distinct families of transporters. Interestingly, the first cloned nitrate transporter in Arabidopsis, NRT1.1 functions as a dual-affinity transporter, which can change its affinity for nitrate in response to substrate availability. Phosphorylation of a threonine residue, Thr101, switches NRT1.1 from low- to high-affinity state. Recent structural studies have unveiled that the unmodified NRT1.1 transporter works as homodimers with Thr101 located in close proximity to the dimer interface. Modification on the Thr101 residue is shown to not only decouple the dimer configuration, but also increase structural flexibility, thereby, altering the substrate affinity of NRT1.1. The structure of NRT1.1 helps establish a novel paradigm in which protein oligomerzation and posttranslational modification can synergistically expand the functional capacity of the major facilitator superfamily (MFS) transporters.